2018
DOI: 10.2147/clep.s164826
|View full text |Cite
|
Sign up to set email alerts
|

HPV self-sampling in cervical cancer screening: the effect of different invitation strategies in various socioeconomic groups - a randomized controlled trial

Abstract: BackgroundParticipation in cervical cancer screening varies by socioeconomic status. The aims were to assess if offering human papilloma virus (HPV) self-sampling kits has an effect on screening participation among various socioeconomic groups and to determine if two invitation strategies for offering self-sampling influence the participation rate equally.MethodsThe study was based on registry data that were applied to data from a randomized controlled trial (n=9,791) measuring how offering HPV self-sampling a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 41 publications
1
29
1
Order By: Relevance
“…On the other hand, receptivity by women who actually performed self-sampling is high in other countries [26], and about 90% of women who perform self-sampling also have a positive impression of the use of the self-sampling kits in our study. In addition, it is clarified that 97.4% of the subjects prefer self-sampling to sampling by a clinician and this is higher than (62.0%) in a survey performed by Winer et al [19],clarifying that young Japanese women strongly prefer self-sampling compared with women in other countries.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…On the other hand, receptivity by women who actually performed self-sampling is high in other countries [26], and about 90% of women who perform self-sampling also have a positive impression of the use of the self-sampling kits in our study. In addition, it is clarified that 97.4% of the subjects prefer self-sampling to sampling by a clinician and this is higher than (62.0%) in a survey performed by Winer et al [19],clarifying that young Japanese women strongly prefer self-sampling compared with women in other countries.…”
Section: Discussioncontrasting
confidence: 45%
“…Hanley et al [23] mention that the opt-in method which confirmed the intention of wanting or not wanting to send self-sampling kits caused a low return ratio than with the directmailed/opt-out method. Tranberg et al [26] mention also that there were much more women conducting self-sampling in the direct-mailed/opt-out method than women that used the opt-in method (direct: 9.4%, opt-in: 8.3%). Therefore, our result has a higher value in this comparative study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…on subgroup-specific attitudes and beliefs about self-collection (De Alba et al, 2008;Forrest et al, 2004;Howard et al, 2009;Ilangovan et al, 2016;Lofters et al, 2017;Montealegre, Mullen, Jibaja-Weiss, Vargas Mendez, & Scheurer, 2015;Vahabi & Lofters, 2016;Virtanen et al, 2014) all the way through regional and national implementation with subgroup analysis for differences in uptake depending on delivery method (Kobetz et al, 2018;Tranberg et al, 2018). Three studies focused on CCS completion rates in the self-collection group versus standard clinic-based collection (Sewali et al, 2015;Virtanen et al, 2015;Virtanen, Anttila, Luostarinen, & Nieminen, 2011).…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
“…top three countries of origin: Syria 12.6%, Turkey 10.5%, Lebanon 7.9%; Tranberg et al, 2018). In the studies conducted in Finland using population-based screening registries, immigrants were distinguished only by the fact that their native language was not either Finnish or Swedish, the two official languages of the study country (Virtanen et al, 2011(Virtanen et al, , 2014(Virtanen et al, , 2015.…”
Section: Defining "Immigrant"mentioning
confidence: 99%